2010
DOI: 10.1002/mrc.2667
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of NMR parameters for phosphate materials

Abstract: In this short review, we discuss the ability to reproduce NMR parameters in the case of phosphates materials through electronic structure calculation within density functional theory linear response. Indeed, the gauge-including projector-augmented wave is today largely used by the solid-state NMR community as a tool for structural determination and it has been applied to a large variety of materials. We emphasise on the crucial points that should be taken into account to perform such calculations. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…Conversely, the sensitivity of the NMR parameters to small changes in structure could enable different structural models or proposals to be validated or refined, if the NMR parameters could be accurately predicted and compared with experiment. Recent work has shown that periodic DFT calculations can successfully predict 31 P and 27 Al NMR parameters for AlPOs (following appropriate optimization, as discussed in detail by Sneddon et al). In this work, crystal structures were taken from the literature (see Table ) and optimized as described above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the sensitivity of the NMR parameters to small changes in structure could enable different structural models or proposals to be validated or refined, if the NMR parameters could be accurately predicted and compared with experiment. Recent work has shown that periodic DFT calculations can successfully predict 31 P and 27 Al NMR parameters for AlPOs (following appropriate optimization, as discussed in detail by Sneddon et al). In this work, crystal structures were taken from the literature (see Table ) and optimized as described above.…”
Section: Resultsmentioning
confidence: 99%
“…It is often necessary to optimize the geometry to an energy minimum in order to obtain good agreement with experimental NMR spectra . The use of semiempirical dispersion‐correction (SEDC) schemes has been demonstrated to have a significant impact on the longer‐range structures obtained after DFT optimization for calcined and as‐prepared AlPOs, with structures optimized using SEDC schemes having better agreement between calculated and experimental NMR and XRD parameters …”
Section: Introductionmentioning
confidence: 99%
“…where σ re f is the chemical shielding tensor for a reference compound. It has been established that the DFT gauge-including projector augmented wave (GIPAW) method (used here) has a linear relationship between the variation in the experimental (δ exp ) and calculated chemical shifts δ calc [36], and that σ exp re f and σ calc re f are not necessarily equivalent. This linear variation is given by…”
Section: Chemical Shift Referencingmentioning
confidence: 99%
“…12 The GIPAW approach was first used for NMR spectral assignments by Profeta and coworkers in silicates 13 and has since been applied to a wide range of organic and inorganic compounds, including sodium perovskites, 14 organic solids, 15,16 aluminum oxides, 17 and phosphates. [18][19][20][21][22][23][24][25][26]…”
Section: Introductionmentioning
confidence: 99%